Enhancing thermal-hydraulic performance of counter flow mini-channel heat sinks utilizing secondary flow: Numerical study with experimental validation. (February 2020) - Tikadar, Amitav; Paul, Titan C.; Oudah, Saad K.; Abdulrazzaq, Nabeel M.; Salman, Azzam S.; Khan, Jamil A.
Abstract: Continual growth of hydraulic and thermal boundary layers along stream wise direction in conventional straight fin mini-channel heat sink (MCHS) causes gradual deterioration of their thermal performance. To enhance thermal-hydraulic performance by breaking and re-development of the boundary layers, this research aims to introduce a novel water cooled inter-connected counter flow mini-channel sink (ICMCHS). Two inter-connectors (ICs) were positioned transversely between two counter flow mini-channels (CMCs) which segmented the flow domain into three zones (zone 1–3). Secondary flow was generated through the ICs utilizing the pressure difference of the adjacent CMCs resulting in disruption of the hydraulic and thermal boundary layers. To examine the effect of the ICs location and width on the thermal-hydraulic characteristics of the counter flow mini-channel heat sink (CMCHS), the present numerical studies were carried out for nine different cases (case 1–9) by varying ICs width from 1 mm to 1.5 mm and ICs location from 4 mm to 9 mm. A corresponding conventional CMCHS was chosen as the base case in contrast to the newly proposed ICMCHS. Experiments were also carried out for CMCHS to validate numerical results, and excellent agreement was found between measured values and the corresponding numerical results. At the lowest considered Re ( Re = 150), a maximum value of Performance Evaluation Criterion (PEC) was achieved to 1.22 for the highest length of zone 1 and 3 and the lowest ICs width (case 7), whereas at the highest Re ( Re = 1044), the maximum PEC value ( 1.42) was recorded for the intermediate length of zone 1 and 3 and the highest ICs width (case 6).